Ischemia with no obstructed coronary arteries and microvascular testing procedures: a review of utility, pharmacotherapy, and current challenges - Al Bitar, Mohammad; Shantouf, Ronney; Al Azzoni, Ashraf; Al Mahmeed, Wael; Atallah, Bassam (Frontiers in Cardiovascular Medicine, 2025)
Ischemia with no obstructive coronary arteries (INOCA) is an increasingly recognized condition in patients presenting with angina and positive stress tests but without significant coronary artery stenosis. This review addresses the pathophysiology, diagnostic approaches, and management strategies associated with INOCA, emphasizing epicardial coronary spasms and coronary microvascular dysfunction (CMD) as underlying mechanisms and myocardial bridging (MB) as a risk factor. Diagnostic modalities include both non-invasive techniques and invasive procedures, such as acetylcholine provocation testing, to differentiate vasospasm from microvascular causes. The paper discusses a potential interference between vasodilators used in trans-radial access and coronary spasm testing. Long-term management approaches for INOCA patients, including pharmacologic therapies and lifestyle interventions, are reviewed.